Protamine mRNA ratio in stallion spermatozoa correlates with mare fecundity. (7th April 2014) - Paradowska‐Dogan, A.; Fernandez, A.; Bergmann, M.; Kretzer, K.; Mallidis, C.; Vieweg, M.; Waliszewski, P.; Zitzmann, M.; Weidner, W.; Steger, K.; Kliesch, S.
Summary Highly compacted sperm DNA in protamine toroids and a minor fraction of nucleohistones are prerequisites for the efficient transmission of the paternal genome into the oocyte at fertilization. The objective of this study was to evaluate whether protamines might serve as a prognostic factor for stallion fertility. In situ hybridization detected specific expression of P1 mRNA in the cytoplasm of stage I to VII spermatids, whereas comparable immunohistochemical stainings showed that protein expression was delayed till elongating spermatids in differentiation stages III to VIII. No staining was detectable in cryptorchid testis because of the lack of spermatids in the seminiferous tubules. Using quantitative real‐time polymerase chain reaction, we identified mRNA transcripts of P1 and 2 variants of protamine‐ 2 (P2, P3) in ejaculated spermatozoa from 45 thoroughbred stallions. According to the mare fertility descriptor (i.e. the 'none‐return‐rate 28 percentage' or NRR28%), stallions were divided into three groups (i.e. high, reduced and low fertility). The P2/P1 mRNA ratio was found to be significantly reduced in the group with lower fertility (p = 0.016) and was slightly correlated with sperm concentration (correlation coefficient r = 0.263). Furthermore, morphologically abnormal sperm count negatively correlated with P2/P1 mRNA ratio, indicating that spermatozoa carrying head defects display a diminished protamine ratio (r = −0.348). Conversely, the P2/P1 ratio was positively correlated with mare fertility or NRR28% (r = 0.274). Interestingly, P3/P1 mRNA ratio remained unaltered in the investigated groups indicating that this variant plays a minor role in equine sperm chromatin compaction. Aberrant protamine transcripts content in equine spermatozoa was not associated with DNA defragmentation rate as measured by flow cytometric acridine orange test. On the basis of these results, we suggest that, similar to human, equine protamine expression constitutes a checkpoint of spermatogenesis and as a corollary the level of protamine mRNA may reflect the quality of spermatogenesis and spermatozoa's fertilizing capacity.